Proposal of a forest physical model for ecological capability evaluation in Zagros vegetation zone (Case study: Masby region, Abdanan city, Ilam province) - Ali Najafifar (تحقیقات جنگل و صنوبر ایران, 2010)
In this research tentative model was determined by GIS for evaluation of the ecological capability in Zagros forests. The study was carried out in Masbei area [Oak (Quercus brantii Lindl.) forests] located in south aspects of Kabirkooh in Ilam province. This model was designed in five different classes and forest evaluation process was done in quantitative form using the model. In order to ecological evaluation in the study area, some factors including altitude, aspect, slope, climate, land form and soil depth were applied. The results obtained from this model showed that there are 425 different ecological situation in 7436 ecological final unit within the study site. Coefficient of determination (R2=0.56) between potency gradations of ecological potential and mean height of trees in 64 field plots (0.15 ha) showed that this model is fairly suitable efficient for ecological potency evaluation in Zagros forests.